The Palgrave Handbook of Cross-Border Journalism
XXV, 618 p. 7 illus., 3 illus. in color.
Keywords: This Handbook analyzes cross-border news production and transnational journalism cultures driven by technological developments in the age of the Internet and the consequences of globalization in all areas of life. It provides an overview of the theoretical and methodological challenges involved in analyzing cross-border journalism, not only looking at the different developments around the world but also offering insights from the perspective of journalistic practitioners. In 38 chapters, renowned experts examine cross-border journalism from both conceptual and empirical perspectives and set the agenda for future research in the international context. The handbook is divided into six sections dealing with the history and conceptualization of cross-border journalism (section 1), the actors and production of cross-border journalism (2), the content of cross-border journalism (3) as well as its audiences (4), regional differences and similarities (5), and its future (6), which is particularly influenced by automation, artificial intelligence, virtual reality, and economic developments.